Perceptions of Saudi Plastic Surgery Residents and Attendings of Online Education during the COVID-19 Pandemic - Kattan, Abdullah E. (Plast Reconstr Surg Glob Open, 2021)
BACKGROUND: The world has faced an unprecedented challenge in controlling the spread of COVID-19—a rapid reshaping of the healthcare system and education was inevitable. Consequently, residency programs adopted e-learning as a social distancing tool for the continuity of the learning process. In this study, we explore the opinions and perspectives of plastic surgery attending doctors and residents on the implications of e-learning. METHODS: After obtaining ethical approval, this cross-sectional study was conducted electronically between October and December 2020 among plastic surgery residents and board-certified plastic surgeons in Saudi Arabia. Participants completed a validated, anonymous, self-administered questionnaire. The questionnaire gathered participants’ demographic data, perceptions of online webinars, and audiovisual evaluations. Finally, we compared traditional (in-person) teaching with online webinars. The analysis was performed at a 95% confidence interval using the Statistical Package for Social Sciences (SPSS), version 23.0 (IBM, Armonk, N.Y.). RESULTS: A total of 61 responses were included in this study. The majority of respondents (78.7%) were comfortable during webinars, with 38 (62.3%) believing they should supplement traditional teaching methods. Overall, 50.8% were satisfied with the webinars. However, 37.7% were neutral. Most believed that the webinars increased their clinical (67.2%) and surgical skills (67.2%) to reasonable levels. CONCLUSIONS: Online education provided an excellent educational tool as a viable option to supplement traditional face-to-face training, with most residents being satisfied, supporting the use of this educational tool. More objective research is required to refine existing online plastic surgery teaching methods while creating novel distance e-learning approaches for the future.